Association between P2RY12 Gene Polymorphisms and IVIG Resistance in Kawasaki Patients. (10th March 2020) - Wang, Zhouping; Xu, Yufen; Zhou, Huazhong; Wang, Yanfei; Li, Wei; Lu, Zhaoliang; Jiang, Zhiyong; Gu, Xueping; Zheng, Hao; Zeng, Lanlan; Huang, Ping; Zhang, Li; et al.
Abstract : Children with Kawasaki disease (KD) resistant to intravenous immunoglobulin (IVIG) have a higher incidence of coronary artery lesions (CAL). Despite the association between Purinergic receptor P2Y12 (P2RY12) polymorphism, KD genetic susceptibility, and CAL complications being proved, few studies have assessed the relationship between P2RY12 polymorphisms and IVIG resistance in patients with KD. We recruited 148 KD patients with IVIG resistance and 611 with IVIG sensitivity and selected five P2RY12 polymorphisms: rs9859538, rs1491974, rs7637803, rs6809699, and rs2046934. A significant difference in the genotype distributions between patients was only observed for the rs6809699 A > C polymorphism (AC vs. AA: adjusted odds ratio (OR) = 0.48, 95% confidence interval (CI) = 0.27–0.84, P = 0.011 ; AC/CC vs. AA: adjusted OR = 0.47, 95% CI = 0.27–0.83, P = 0.0084 ). After adjusting for age and gender, the carriers of the rs6809699 C allele had OR of 0.44 to 0.49 for IVIG sensitivity (AC vs. AA: adjusted OR = 0.48, 95% confidence interval (CI) = 0.27–0.84, P = 0.011 ; AC/CC vs. AA: adjusted OR = 0.47, 95% CI = 0.27–0.83, P = 0.0084 ) compared to the carriers of a rs6809699 AA genotype, suggesting the protective effect of this SNP against IVIG resistance. Moreover, individuals with all five protective polymorphisms experienced a significantly decreased IVIG resistance compared to that of individuals with up to three protective polymorphisms (adjusted OR = 0.27, 95% CI = 0.13–0.57, P = 0.0006 ). Our results suggest that the P2RY12 rs6809699 polymorphism could be used as a biomarker to predict IVIG resistance in KD patients.